HYDROGEN PRODUCED BY SOLAR ENERGY AND THEIR USE AS CLEAN FUEL FOR POWER GENERATION IN A COMBINED CYCLE POWER PLANT - Restrepo, J. C.; Venturini, O. J.; Silva, E. E.; Cortabarria, L. A. (Revista de Engenharia Térmica, 2016)
The solar energy is one of the most promising energy sources expected for the future, due at their huge potential and the wide availability around the world. However, nowadays this important source of energy is not being harnessed or even addressed in their full potential. According to the last statements, it is important to develop solar energy conversion systems of high efficiency, as well as spreading its use in other forms besides the traditional systems of electric power generation or heating systems. For this reason, in this paper, it is explored the production of hydrogen through solar energy utilization, and the later electrical energy production by burning the produced hydrogen in a combined cycle power plant. The process was modelled for 3 MWe of electricity generation, and using the organic Rankine cycle. The main process for producing hydrogen from water using solar energy is based on a two steps redox thermochemical cycle, which has a theoretical conversion efficiencies of 54% at 1600 K. It is expected that this paper could contributed to the development of ways to enable a better integration of the solar energy with the current electricity generation technologies, as well as to incentive the use of the hydrogen as a clean fuel.